KETERLIBATAN MASYARAKAT LOKAL ANGGOTA KOPERASI PRODUSEN “EBIER SUTH” COKRAN DALAM KEGIATAN USAHATANI KAKAO DI KAMPUNG ABRESO DISTRIK RANSIKI - Medtramisia Meriani Rumwaropen; Umi Yuminarti; Yustina. L. D. Wambrauw (Sosio Agri Papua, 2021)
Local Community Involvement. Cooperative members are local people who participate in carrying out their duties, rights and responsibilities in cocoa farming activities. This study aims to (1) Know the stages of the cocoa production process in the “Ebier Suth” Cokran Producers' Cooperative (2) Know the stages of the post-harvest management process for cocoa beans in the “Ebier Suth” Cokran Producer's Cooperative (3) Know the involvement of local communities in the cocoa farming activities of the Cokran “Ebier Suth” Producer's Cooperative. The method used in this research is descriptive method through a case study approach. The data in this study were analyzed using tabulation using descriptive methods, to be able to answer about the involvement of local communities in cocoa farming activities and to determine the stages of the cocoa production process, and the stages of the post- harvest cocoa management process at the “Ebier Suth” Cokran Producer's Cooperative. . Based on the analysis results obtained 5 stages of the production process and 4 stages of the post- harvest management process of cocoa. The involvement of local communities is quite large in the production process and in the management process, the number of local people is small and not many are involved.